2019
DOI: 10.1021/acs.energyfuels.9b02540
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Ignition of a Hexadecane Droplet Mixed with Different Octane Number Fuels at Elevated Pressures To Investigate the Pre-Ignition Behavior

Abstract: Pre-ignition is an abnormal combustion event that may occur in boosted direct injection gasoline engines, where one or more auto-ignition events are observed before spark ignition. Due to the direct injection of fuel into the cylinder, some liquid fuel may splash off the walls, pulling lubricating oil with it. The auto-ignition of liquid fuel/lubricant droplets is considered as one of the possible sources of pre-ignition. To assess this stochastic phenomenon in a controlled way, the autoignition of a single dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The piston's movement is regulated by pneumatic solenoid valves (Peter Paul Electronics Co. EH22H90CCH6) within the actuator cylinder. Further experimental details can be found in ref 24.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The piston's movement is regulated by pneumatic solenoid valves (Peter Paul Electronics Co. EH22H90CCH6) within the actuator cylinder. Further experimental details can be found in ref 24.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
“…Previous studies have shown hexadecane to be a suitable surrogate for lubricant oil as it shows similar ignition characteristics. ,, Hence, hexadecane has been considered as a surrogate for lubricant oil in this study. Previously, Mitsudharmadi et al investigated the effect of RON of different fuels by mixing FACE I, PRF91, PRF95, and toluene with hexadecane by 25 vol % in pre-ignition occurrences. Their investigation showed that the effect of RON did not affect the auto-ignition of the mixtures for pressures above 20 bar.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the phase behavior of higher alkanes, which are petroleum or fuel ingredients, with atmospheric gases, such as nitrogen, is of importance for operations that take place at elevated temperature and pressure conditions . Those processes are, for example, the petroleum recovery in deep reservoirs, as well as the steps inside a diesel engine, such as injection, mixture formation, and ignition. , Especially for the latter, certain alkanes such as n -hexadecane are regarded as a diesel-surrogate component in many publications. Therein diesel is described as a binary, ternary, or another multicompound system, for which the physical and chemical properties, as well as combustion kinetics, are comparable to the values of a real fuel. , …”
Section: Introductionmentioning
confidence: 99%